Econometrical Analysis of the Demand for Entrance Tourism in Kazakhstan - Kuralbayev, Almas; Sevim, Burhan; Abishev, Nurjan (International Journal of Economics and Financial Issues, 2017)
The article deals with the modeling the demand for inbound tourism in Kazakhstan and in the regions. The panel data for 16 countries was used - the basic sources of tourist flows and the period from 2010 to 2014. Modeling is carried out separately for the South-Kazakhstan region of 5 tourist zones. As the determinants of demand the gross national product in the country of origin, exchange rate, transport costs, cost of living and the lagged demand variable was considered. The estimates of dynamic models of demand correspond to the expectations, are statistically significant and can be useful in the practice of development planning of tourism in different municipalities and regions of Kazakhstan. Keywords: demand for entrance tourism, tourist areas, tourist flows, dynamic model, panel data. JEL Classifications: O18, Z30, Z39